Love the Truth in the Franciscan School (XIIIth century) - Lázaro Pulido, Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Love to the truth is a fundamental question in the Franciscan School. It has your origin on the Franciscan practical needs to transmit the evangelical message to all the men. The universality of the message inspires the concept of wisdom as a base to love the truth. The truth appears as occasion of reference to God, the significatio never subordinates to the res. The article exposes the fundamental milestones of this construction from the origins of the Franciscan School to the ends of the 13th century with Gonzalo Hispano, indicating the common points and the internal discussions of a School according Anthony of Lisbon/Padua, Alexander of Hales, Odo Rigaldus, William of Melitona, Robert Grosseteste, Roger Bacon, Bonaventure, Matthew of Aquasparta, Peter John Olivi and Gonsalvus of Spain